Compendium of International and National Legal Frameworks on Female Genital Mutilation, Fourth Edition - World Bank (World Bank, Washington, DC, 2020)
Female Genital Mutilation/Cutting (FGM/C) is a development issue and a form of violence against women and girls that affects at least 200 million women in the world FGM/C is a harmful practice proven to impact the physical and mental health of affected women and girls from the moment of the cutting, with prolonged and irreversible consequences during their entire lives. Studies show that FGM/C has economic and social consequences and a high obstetric cost although a comprehensive study on the exact extent of these economic, health and social costs is still to be carried out. Beyond the data and the statistics, researcher have shown that FGM/C deprives women of sexual satisfaction, sexual health and psychophysical wellbeing. The Compendium of International and National Legal Frameworks on Female Genital Mutilation (the "Compendium") was prepared to contribute to this urgent and important development debate with the understanding that the knowledge of the law is an important empowerment tool to end FGM/C. It provides a survey of the key international and regional instruments as well as domestic legislation as they relate to the prohibition of FGM/C.